Design de Aplicação Ubíqua de Aprendizagem para oferecer suporte à conexão entre Cidadãos e o Patrimônio Histórico - da Rocha Seixas, Luma; José de Melo Filho, Ivanildo; Sandro Gomes, Alex; Maria de Melo, Rosangela (RENOTE, 2018)
This article aims to explore the generation of connections between citizens and historical heritage, made possible through the design of a mobile application with characteristics of ubiquitous learning to support informal learning about historical places. The methodological process followed the recommendations of the Design Science Research Methodology (DSRM). Among the steps that make up the DSRM, this research reports the steps related to the process of design and design of the application. The results obtained after the execution of the phases that make up this stage allowed the generation of a functional version of the application aligned with the proposed objectives that seeks to broaden the perception of the citizens about the Historical Patrimony of the place where they are.